The Development of Teaching Materials for Writing Exposition Text Using the Application of Lectora Inspire Oriented Critical Thinking Skill and Containing the Values of Deliberation - Lutfianti, Kartika Dewi; Subyantoro, Subyantoro; Haryadi, Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The use of inappropriate and less innovative teaching materials causes the learning process to be less impressive. This has an impact on the limited ability, knowledge, experience, and creativity of students. This study aimed to develop a prototype of teaching materials for writing exposition texts using the application of Lectora Inspire, which was oriented towards critical thinking skills and contained the value of deliberation. This research used Research and Development (R&D) design that using data on the needs of students and teachers for teaching materials. The results of this study were prototypes of teaching materials for writing exposition texts using the Lectora inspire application, which was oriented towards critical thinking skills and contained the value of deliberation. Prototypes of teaching materials were prepared based on the results of the analysis of data needs and the principles of developing teaching materials. The prototype of the introductory teaching materials used existing principles in the presentation and graphic aspects, namely the principles of integration, convenience, and usability. The prototype of teaching materials for the content section used existing principles in the aspects of material, presentation, critical thinking skills, and the value of deliberation, namely the principles of completeness, attractiveness, integration, convenience, and novelty. The prototype of teaching materials for the closing section used the principles in the presentation aspect, namely integration and convenience. In addition to these principles, there were other principles in the linguistic and application aspects, namely communicativeness, convenience, and novelty. These principles were used to develop an overall prototype of teaching materials.